2004
DOI: 10.1063/1.1713035
|View full text |Cite
|
Sign up to set email alerts
|

Bias-induced threshold voltages shifts in thin-film organic transistors

Abstract: Articles you may be interested inControl of threshold voltage in organic thin-film transistors by modifying gate electrode surface with MoOX aqueous solution and inverter circuit applications Appl. Phys. Lett. 106, 053301 (2015); 10.1063/1.4907317Analyzing the influence of negative gate bias stress on the transconductance of solution-processed, organic thinfilm transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(109 citation statements)
references
References 21 publications
8
100
0
1
Order By: Relevance
“…Under vacuum conditions, with practically no water present on the SiO 2 interface, the bias-stress effect is greatly slowed down. 6,11,20,21 This is evident from the relaxation time of =2ϫ 10 6 s obtained from the bias-stress measurements on a similar PTAA transistor in vacuum, 11 which is more than two orders of magnitude larger than the above value in ambient. Furthermore, pretreatment of the SiO 2 with hydrophobic HMDS or octadecyltrichlorosilane is is known to decelerate the effect.…”
Section: Bias-stress Effect: Experimentalmentioning
confidence: 73%
See 2 more Smart Citations
“…Under vacuum conditions, with practically no water present on the SiO 2 interface, the bias-stress effect is greatly slowed down. 6,11,20,21 This is evident from the relaxation time of =2ϫ 10 6 s obtained from the bias-stress measurements on a similar PTAA transistor in vacuum, 11 which is more than two orders of magnitude larger than the above value in ambient. Furthermore, pretreatment of the SiO 2 with hydrophobic HMDS or octadecyltrichlorosilane is is known to decelerate the effect.…”
Section: Bias-stress Effect: Experimentalmentioning
confidence: 73%
“…2͑a͒ show the thresholdvoltage shift ⌬V th ͑t͒ = V th 0 − V th ͑t͒ as a function of time t. Here, V th 0 is the threshold voltage shift at the start of the experiment, which is close to zero. In studies of the bias-stress effect it has become customary to describe the shift ⌬V th ͑t͒ with a stretched-exponential function, 6,11,16 ⌬V th ͑t͒ = V 0 ͑1 − exp͓−͑t / ͒ ␤ ͔͒, where the prefactor V 0 is close to ͉V G0 ͉, is a relaxation time, and 0 Ͻ ␤ Ͻ 1 an exponent. As can be seen in Fig.…”
Section: Bias-stress Effect: Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress effects are commonly reported in the literature for a variety of transistors prepared using different techniques, different dielectric layers, as well as different organic semiconductors. [1][2][3][4][5][6][7] The effect has been explained as due to a slow trapping of charge carriers in defects of unknown origin. 3 It is known that the current degradation is faster when the devices are exposed to water vapor atmosphere, 4 moreover it has been also reported that the device electrical stability improves after heating the devices in high vacuum.…”
mentioning
confidence: 99%
“…The shift in threshold voltage leads to a monotonically decreasing source-drain current. Experimentally, it has been shown that the threshold-voltage shift follows a stretchedexponential time dependence [4][5][6] as given by DV th ðtÞ ¼ ðV G À V th;0 Þð1 À exp½Àðt=sÞ b Þ;…”
mentioning
confidence: 99%